THE CUISINE OF THE EDE PEOPLE IN KMRONG PRŎNG VILLAGE, BUON MA THUOT (DAK LAK PROVINCE) - Bao Tram Pham; Niê Y Dhiư; Dac Tu Truong; Quang Nam Tran (Tạp chí Khoa học Đại học Đà Lạt)
The Ede are a Malayo-Polynesian language-speaking ethnic group residing primarily in Dak Lak, Dak Nong, Phu Yen, and Khanh Hoa provinces. They have a rich and unique tangible and intangible culture. From 2017 to 2020, the authors carried out many field trips to Kmrong Prŏng A and Kmrong Prŏng B villages (Ea Tu Commune, Buon Ma Thuot) to research, collect, and inventory the material and spiritual cultural heritage of the Ede for conservation and exhibition at the Dak Lak provincial museum. In this article, we introduce some traditional dishes of the Ede in Krmong Prŏng village, research and evaluate traditional aspects of their cuisine, and propose some recommendations and solutions to preserve and promote the unique Ede cuisine in the current period of development and integration.